1990
DOI: 10.1007/bf02245743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol on reinforced repetitions and reinforced variations in rats

Abstract: Six rats were rewarded with food pellets for repeating a particular sequence of four responses on two levers, namely left-left-right-right. Ethanol (0.75 g/kg and 2.0 g/kg injected IP) increased the variability of sequences under these "repeat" contingencies, resulting in fewer rewarded trials. Six other rats were rewarded only if their sequence of left and right responses in the current trial differed from each of the previous five trials. Ethanol had little effect on sequence variability and no effect on rew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
0
5

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 22 publications
7
23
0
5
Order By: Relevance
“…They also indicate a dissociation similar to that described by Grunow and Neuringer (2002): Response rates were primarily controlled by reinforcement frequencies (in Grunow & Neuringer, 2002) and delays (in the present experiment), whereas response variability was primarily controlled by reinforcement contingencies in both experiments. The results are consistent as well with previous studies showing that reinforced variability is relatively immune to adverse impact from other reinforcementweakening events (Cohen et al, 1990;Doughty & Lattal, 2001;Grunow & Neuringer, 2002;McElroy & Neuringer, 1990;Neuringer, 1991).…”
Section: Discussionsupporting
confidence: 92%
“…They also indicate a dissociation similar to that described by Grunow and Neuringer (2002): Response rates were primarily controlled by reinforcement frequencies (in Grunow & Neuringer, 2002) and delays (in the present experiment), whereas response variability was primarily controlled by reinforcement contingencies in both experiments. The results are consistent as well with previous studies showing that reinforced variability is relatively immune to adverse impact from other reinforcementweakening events (Cohen et al, 1990;Doughty & Lattal, 2001;Grunow & Neuringer, 2002;McElroy & Neuringer, 1990;Neuringer, 1991).…”
Section: Discussionsupporting
confidence: 92%
“…(Counting in binary, and arbitrarily assigning L = 0 and R = 1, these are sequences 0, 7, and 1, respectively.) Previous research had shown that when V ARIA TION AND SELECTION 85 reinforcement was provided independently of sequence variability in a two-lever chamber, rats were most likely to respond on a single lever and that LRRR was more likely to occur than LLLR (e. g., McElroy & Neuringer, 1990;Morgan & Neuringer, 1990;Neuringer & Huntley, 1992). We therefore hypothesized that LLLL would most readily be strengthened by an always contingency and that LRRR would more readily be strengthened than LLLR.…”
Section: Experiments 2 Selection As a Function Of Sequence Difficultymentioning
confidence: 94%
“…McElroy and Neuringer (1990) reported that alcohol may lead to increases in both response variability and response stereotypy. They administered alcohol to 2 groups of animals, 1 of which was given training to perform a task requiring sequence variability; the other was given training to perform a task requiring sequence repetition.…”
Section: Other Factors That Influence Response Variabilitymentioning
confidence: 99%